The effect of leverage and capital intensity on tax avoidance with institutional ownership as a moderating variable - Anggraini, Fitria; Wijaya, Suparna (Educoretax, 2024)
This research is a quantitative study that aims to analyze the effect of leverage and capital intensity on tax avoidance with institutional ownership as a moderating variable. This research is a quantitative study using secondary data in the form of audited financial reports on Primary Consumer Goods sector companies listed on the Indonesia Stock Exchange for the period 2019 - 2023. The sample selection method used purposive sampling technique with several criteria and 304 samples were used in this study. The data analysis used in this study is descriptive statistical analysis, parameter significance test (t test), and determination coefficient test using STATA v.17.0 software with a significance level of 5% (0.05). The results of this test obtained (1) there is no significant effect of leverage on tax avoidance, (2) there is no significant effect of capital intensity on tax avoidance, (3) institutional ownership is not able to moderate the effect of leverage on tax avoidance, (4) institutional ownership is not able to moderate the effect of capital intensity on tax avoidance.